Advances in intelligent data analysis XIV : 14th international symposium, IDA 2015, Saint Etienne, France, October 22-24, 2015 : proceedings /: 14th international symposium, IDA 2015, Saint Etienne, France, October 22-24, 2015 : proceedings. (2015) - Unknown
No abstract available